CURRENT STAGE OF HOMOLOGATION OF THE FIRST ROMANIAN RABBIT BREED – TRANSYLVANIAN GIANT RABBIT - Malina Petrescu-Mag, Ruxandra; Petrescu-Mag, Ioan Valentin; Crina Petrescu, Dacinia; Creanga, Steofl (Economics of Agriculture, 2018)
The paper presents the current state of the homologation process of the first Romanian rabbit breed. Animal production very often takes into account aspects such as conservation of national genetic resources, but also an improved productivity. These two issues are the main reasons for creating the first rabbit breed in Romania: Transylvanian Giant Rabbit Breed. We point out here our latest scientific achievements – accomplished during 2011.